Honokiol inhibits Vibrio harveyi hemolysin virulence by reducing its haemolytic activity. (19th October 2019) - Guo, Yi; Xing, Zhenyu; He, Zhe; Zhao, Xiaoran; Ye, Shigen
Abstract: Vibrio harveyi, as one of the main pathogens of vibriosis, has serious multidrug resistance, which has been a focus for domestic and foreign researchers. Vibrio harveyi hemolysin (VHH), an important virulence determinant of V. harveyi, causes cell necrosis and tissue damage by lysing cell membranes, which is essential for V. harveyi invasion of the host. The critical role of VHH in the virulence of V. harveyi renders it an ideal target for designing novel anti‐virulence therapeutics. We found that honokiol, a natural compound, could act as a potent antagonist of VHH‐mediated haemolysis at non‐bacteriostatic concentrations. Honokiol can effectively inhibit the damage caused by VHH and V. harveyi both in vitro and in vivo. qRT‐PCR and molecular docking analysis showed that although honokiol up‐regulated the transcription level of vhh, it could block the active centre of VHH directly and forcefully, thereby reducing the catalytic activity of VHH. The results suggest that HNK could have great potential in the development of new aquaculture drugs.